2022
DOI: 10.3390/polym14235116
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Egg White Dual Cross-Linked Hydrogel with Potential Application for Bone Tissue Engineering

Abstract: In this study, an egg white dual cross-linked hydrogel was developed based on the principle that the external stimulus can denature proteins and cause them to aggregate, forming hydrogel. The sodium hydroxide was used to induce gelation of the egg white protein, subsequently introducing calcium ions to cross-link with protein chains, thereby producing a dual cross-linked hydrogel. The characteristics of the dual cross-linked hydrogels—including the secondary structure, stability, microstructure, swelling perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…EW has also garnered interest in bone regeneration research; its biocompatibility and antibacterial characteristics significantly improve the performance of bone/dental biomaterials, especially in in vivo studies [52,54,[73][74][75]. Notably, Patty et al developed a nanocomposite with EW, where ovalbumin significantly affected the pore sizes and porosity of their bone biomaterials, and controllable pore sizes and porosity could be achieved by involving different concentrations of EW [73].…”
Section: Egg White (Ew)mentioning
confidence: 99%
See 1 more Smart Citation
“…EW has also garnered interest in bone regeneration research; its biocompatibility and antibacterial characteristics significantly improve the performance of bone/dental biomaterials, especially in in vivo studies [52,54,[73][74][75]. Notably, Patty et al developed a nanocomposite with EW, where ovalbumin significantly affected the pore sizes and porosity of their bone biomaterials, and controllable pore sizes and porosity could be achieved by involving different concentrations of EW [73].…”
Section: Egg White (Ew)mentioning
confidence: 99%
“…The study showed that cells grown on EW-Alginate (EWA) scaffold had comparable spheroid size to cells grown on Matrigel ® over 3 weeks. Similarly, Duan et al developed an EW dual crosslinked hydrogel with sodium hydroxide and CaCl 2 , and they found that increasing the concentration of calcium ions (from 0% to 4%) decreases the porosities of their hydrogels and the equilibrium swelling ratio [74].…”
Section: Egg White (Ew)mentioning
confidence: 99%
“…The nanoparticles exhibit excellent particle size dispersion, uniform morphology, effective drug release performance, favorable biocompatibility, and can effectively inhibit CT26 colorectal cancer cells in vitro In addition, the mechanical properties of EW materials also can be improved through cross-linking. With the addition of cross-linking agents such as methyl vinyl ether-maleic acid, carbodiimide, and glutaraldehyde, EW can form 3D scaffold materials with improved mechanical properties, which can promote cell adhesion and regeneration. Duan et al used sodium hydroxide to induce the gelation of EW and subsequently introduced calcium ions to cross-link with EW protein chains to prepare a dual cross-linked hydrogel. This hydrogel exhibited biocompatibility and cell-surface adhesion in vitro and showed potential for use in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…With the addition of cross-linking agents such as methyl vinyl ether-maleic acid, carbodiimide, and glutaraldehyde, EW can form 3D scaffold materials with improved mechanical properties, which can promote cell adhesion and regeneration. 18 20 Duan et al 21 used sodium hydroxide to induce the gelation of EW and subsequently introduced calcium ions to cross-link with EW protein chains to prepare a dual cross-linked hydrogel. This hydrogel exhibited biocompatibility and cell-surface adhesion in vitro and showed potential for use in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%